Analisis perilaku kinerja struktur bangunan pada variasi tipe podium zona gempa 5 menggunakan metode respon spektrum - Paskalis Halawa; Sudarno P Tampubolon; Lolom Evalita Hutabarat (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Buildings or structures in Indonesia are highly vulnerable to earthquakes, especially in seismic zone 5. Podium-type buildings consist of two main parts: the podium and the tower. This type of building is used due to its advantages of better stability, resulting from a wider base, efficient land use, and good seismic performance. Therefore, this study aims to analyze the structural behavior of three types of buildings: non-podium structures, centrically supported podium towers, and eccentrically supported podium towers. The analysis is conducted using the response spectrum analysis method to examine various structural behaviors, including comparisons of base shear forces, inter-story drift, and the P-Delta effect. The analysis results show that the base shear force of the non-podium structure is 18,463.26 kN, which is higher than that of the centrically supported podium tower at 10,661 kN and the eccentrically supported podium tower at 10,661 kN. In terms of inter-story drift in the x-direction, the eccentrically supported podium tower (model 3) has a displacement of 64.405 mm, exceeding the permissible limit of 61.538 mm. Meanwhile, the non-podium structure (model 1) has a displacement of 60.658 mm, and the centrically supported podium tower (model 2) has 56.408 mm, both meeting the permissible drift limits. For the maximum P-Delta values, Model 1 is 0.0964, Model 2 is 0.05844, and Model 3 is 0.0722, all of which comply with the P-Delta effect limits. The findings of this study are expected to provide a deeper understanding of the differences in structural performance between non-podium structures, centrically supported podium towers, and eccentrically supported podium towers, which can be used as a reference for designers in selecting a structurally safe system by increasing stability against lateral loads.